Kajian Yuridis Perjanjian Perkawinan Menurut Kitab Undang-Undang Hukum Perdata, Undang-Undang Nomor 1 Tahun 1974 dan Kompilasi Hukum Islam - Sukardi Sukardi (The Pontianak State Institute of Islamic Studies, 2016)
Prenuptial agreement can be used as preparation for entering the household life. Prenuptial agreement is an agreement held before marriage takes place. The history of prenuptial agreement itself was born in western culture, not in Indonesia that still upholds the traditional oriental culture. Even some people consider this to a sensitive issue that is uncommon and considered unusual, rude, materialistic, selfish, unethical, not in accordance with Islamic customs, etc. This research aims to investigate and examine prenuptial agreement in the Civil Code, the Marriage Law and Islamic Law Compilation. The method of this research is a normative legal research which is to conduct the assessment and in depth review of prenuptial agreement, whether the agreement is in accordance with Islamic law and positive law in Indonesia through the collection of books and materials about the prenuptial agreement. The nature of this research is the study of literature which is to examine and study a number of literature through the analysis of the prenuptial agreement. Prenuptial agreement in Indonesia is carried out according to the law applied on each party (husband and wife), both based on the Civil Code, Law No. 1 / 1974 and the Compilation of Islamic Law. Prenuptial agreement is not mandatory. It means that prenuptial agreement is a supplementary agreement binding only when it has been made. In the draft legislation, prenuptial agreement has some similarities and differences both in the Civil Code, Marriage Law and the ILC. The main similarity is that it should be made by a competent authority prescribed by law in this case created by a notary for those who are subject to the Civil Code and by the marriage registrar's office for those who are subject to the Marriage Law and ILC. Prenuptial agreement is formally similar to agreements in general, and the difference is about the content or object of the agreement itself, in this case the Civil Code in principle on property / wealth, while the provisions of prenuptial agreement contained in Marriage Law explicitly does not mention the object of what can be concluded that the agreement can be about various things, as long as it does not conflict with the the law, religion and morality. The provisions of the Compilation of Islamic Law on the object, which is ta'lik, mixing personal property and separating property income.